114k views
5 votes
Simplify (1 − cos x)(1 + cos x). (2 points)

2 Answers

4 votes

Answer:


sin^2x

Explanation:

Given expression,


(1 - cos x)(1 + cos x)

By using
a^2-b^2=(a+b)(a-b)


(1 - cos x)(1 + cos x)=1^2 - cos^2x = 1 - cos^2x


\because sin^2x+cos^2x=1


\implies (1 - cos x)(1 + cos x)=sin^2x+cos^2x - cos^2x=sin^2x

Since, further simplification is not possible,

Hence, the simplified form of the given expression is
sin^2x

User Casr
by
4.9k points
4 votes

Answer:

sin²x

Explanation:

we have

(1 − cos x)(1 + cos x)=1-cos²x

Remember that

sin²x+cos²x=1 ------> i-cos²x=sin²x

therefore

(1 − cos x)(1 + cos x)=sin²x

User Diarmid Roberts
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.